Metabolic syndrome and Framingham risk score in obese young adults (Medical Journal of Indonesia, 2013)
Background: The increase number of the metabolic syndrome (MetS) among young adults was mostly caused by obesity. MetS increases the risk of coronary heart disease (CHD) which can be estimated by Framingham risk score (FRS). The study was aimed to know the prevalence of MetS and FRS in obese young adults and to associate them with the components of MetS. Methods: A total of 70 male and female students aged 18-25 years with BMI ≥25 kg/m2 in Faculty of Medicine Universitas Indonesia were selected consecutively. The blood samples used to test fasting blood glucose, total cholesterol, high-density lipoprotein, and triglyceride were examined in Department of Clinical Pathology, Cipto Mangunkusumo Hospital after fasting for 14-16 hours. International Diabetes Federation (IDF) definition was used to diagnose MetS. Univariate and bivariate analysis were done. Results: The prevalence of MetS based on IDF definition was 18.6% among obese young adults. The most associated MetS components was hypertriglyceridemia (OR 12.13; 95% CI 2.92-50.46; p=0.001), followed with high blood pressure (OR 9.33; 95% CI 2.26-38.56; p = 0.001), low-HDL (OR 8.33; 95% CI 2.17-32.05; p=0.003), and impaired fasting glucose (p=0.03). Four subjects had FRS ≥1% and 66 subjects had risk <1%. Increased FRS was not associated with MetS (p=0.154). There was no component of MetS associated with increased FRS. Conclusion: Prevalence of MetS in obese young adults was similar with obese children and adolescents. Although no association of MetS and FRS was found, they are significant predictors for CHD which should not be used separately.